PENGARUH MANAJEMEN NYERI TERHADAP TINGKAT NYERI PADA PASIEN KOLIK ABDOMEN DI RUANGAN IGD RSUD LABUANG BAJI MAKASSAR - Muhaimin Fajar Pasi; Sudarman; Safruddin; H. Syahril (Jurnal Kesehatan, 2025)
Abdominal colic pain is a common problem in the Emergency Department (ER). The management of abdominal pain is often dominated by pharmacological therapy, even though non-pharmacological therapy is also effective in reducing pain. The purpose of this study is to analyze the effectiveness of pain management on pain reduction in abdominal colic patients in the emergency room of Labuang Baji Makassar Hospital. The research method was a case study with a 1x8-hour nursing approach at Labuang Baji Hospital, Makassar. Data collection was carried out through interviews, direct observation, and physical examination. Nursing interventions include pain management and warm compresses. After 8 hours of implementation, the pain problems in the patient showed a decrease. The patient said his abdominal pain decreased from a scale of 5 to a scale of 3. The client no longer seems to be grimashing and seems relaxed. Vital signs show relatively stable results. Nursing measures are able to effectively manage abdominal colic. A comprehensive approach is needed in providing nursing care, including prevention of nutritional deficits and psychological support.